Self-Selection into Export Markets by Business Services Firms: Evidence from France, Germany and the United Kingdom - Joachim Wagner; Yama Temouri; Alexander Vogel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
This study reports results from an empirical investigation of business services sector firms that (start to) export, comparing exporters to firms that serve the national market only. We estimate identically specified empirical models using comparable enterprise level data from France, Germany, and the United Kingdom. Exporters are more productive and pay higher wages on average in all three countries. Results for profitability differ across borders – profitability of exporters is significantly smaller in Germany, significantly larger in France, and does not differ significantly in the UK. The results for wages and productivity hold in the years before the export start, which indicates self-selection into exporting of more productive services firms that pay higher wages. The surprising finding of self-selection of less profitable German business services firms into exporting does not show up among firms from France and the UK where no statistically significant relationship between profitability and starting to export is found.
Keywords: F14; D21; L80; 330; business services firms; exports; self-selection; France; Germany; UK